Identifikasi Pengaruh Lintasan-Jamak pada DVB-T2 Berdasar Uji Penerimaan Siaran - Budi Setiyanto; Risanuri Hidayat; I Wayan Mustika; Sunarno (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
In many countries, migration from analog to digital in television (TV) broadcasting technology is being in progress. Indonesia has adopted DVB-T2 (Digital Video Broadcasting-Terrestrial Second Generation) as the standard of free-to-air digital TV (DTV) broadcasting system. Frequency selective fading due to multipath propagation affects the reception of this terrestrial radio communication system. This paper presents those effects on reception of DVB-T2 signal from the Yogyakarta transmitting stations. The presence of these effects were identified experimentally, based on several received-signal describing quantities obtained from some field-observations on indoor/outdoor stationary/mobile receptions. Examples of these quantities are spectrum flatness measurement (SFM), signal quality (SQ) versus signal intensity (SI), power level (P) versus carrier-to-noise ratio (CNR), CNR versus modulation error ratio (MER), local variation of reception-success, and received data packet. Several numerical examples are: (1) SFM achieved as high as about 0.7 and 0.9 for indoor and outdoor, respectively, and (2) spatial-probability of reception-success at an indoor receiver location varied from 40,06 % to 81,85 %, approximately.